2018
DOI: 10.1159/000493836
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Release of IGF-1 by 3D Mesoporous Scaffolds Promoting Cardiac Stem Cell Migration and Proliferation

Abstract: Background/Aims: C-kit-positive cardiac stem cells (CSCs) may have potential as a treatment for cardiovascular disease. However, the low survival rates of c-kit-positive CSCs present a major challenge during the transplantation process. Methods: The hierarchical structure of the 3D cell scaffold was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and N2 adsorption-desorption isotherms. Analyses of the proliferation and migration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…A steady release was important as a high concentration could cause various side effects, such as heterotopic bone formation, edema or inflammatory reactions [35]. In order to solve this problem, some studies have used the encapsulation of BMP-2 in micro-or nanoparticles and incorporated in the composite scaffolds [36]. Our previous results have shown that pre-loading of factors into raw materials had better sustained-release profiles as compared to direct loading of factors [19].…”
Section: Bmp-2-released Profilementioning
confidence: 99%
“…A steady release was important as a high concentration could cause various side effects, such as heterotopic bone formation, edema or inflammatory reactions [35]. In order to solve this problem, some studies have used the encapsulation of BMP-2 in micro-or nanoparticles and incorporated in the composite scaffolds [36]. Our previous results have shown that pre-loading of factors into raw materials had better sustained-release profiles as compared to direct loading of factors [19].…”
Section: Bmp-2-released Profilementioning
confidence: 99%
“…During the past few years, nano-porous bioscaffolds have been proven to be good methods for drug delivery and for controlled, sustained release of drug molecules. According to one report, a mesoporous scaffold was loaded with insulin-like growth factor 1 to induce cardiac stem cell proliferation and migration and it was shown to be a potential candidate for in vivo treatment [43]. To investigate whether a higher BMP-2 concentration ratio would increase bone regeneration, we used 3D printing to make nano-pore-sized scaffolds intended to provide a controlled release rate over a 6-month time period.…”
Section: Bmp-2 Releasementioning
confidence: 99%
“…Engineered scaffolds, when paired with patient-specific stem cells, can be used to deliver novel therapies and advance regenerative medicine [46,50]. In the field of cardiac tissue engineering, polymeric biomaterials can be derived from natural or synthetic sources.…”
Section: Hybrid (Cellular Scaffold) Approachesmentioning
confidence: 99%
“…To accurately simulate their target environment, scaffolds require directed assembly of the biomaterial components using various approaches including casting, bioprinting, or electrospinning, which are covered in more detail later in this review. In the case of synthetic scaffolds, polymer functionalization using a variety of small molecules, peptides, and proteins is often required to facilitate cellular integration and maturation within the engineered tissue construct [48,50]. For any of these scaffolds to be a viable long-term translational option, they must support vascularization, either directly, or through their porous structure.…”
Section: Hybrid (Cellular Scaffold) Approachesmentioning
confidence: 99%